Time discounting: The delay effect and procrastinating behavior - Shunichiro Sasaki; Shiyu Xie; Shinsuke Ikeda; Jie Qin; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2008)
The delay effect, that people discount the near future more than the distant future, has not been verified rigorously. An experiment conducted by us in China confirms that, by separating the delay from the interval, the delay effect exists only within a short delay. The results are reliable, because the rewards paid were very large, in order to elicit the subjects' true preferences. The interval and magnitude effects are also confirmed. Finally, subjects' procrastinating behavior, as reported in the questionnaire conducted at the end of the experiment, is explained by the time discount rates and the degree of the delay effect revealed in the experiment.
Keywords: C91; D91; 330; discount rate; economic experiment in China; delay effect; naïfs and sophisticates; procrastination